2016
DOI: 10.1016/j.chom.2016.09.013
|View full text |Cite
|
Sign up to set email alerts
|

ICAM-5/Telencephalin Is a Functional Entry Receptor for Enterovirus D68

Abstract: Enterovirus D68 (EV-D68) is a member of the Picornaviridae family. Although EV-D68-associated infection was once considered rare, it has been increasing in recent years. EV-D68 infection is most frequently associated with respiratory illness. However, it has also been implicated in a polio-like neurological disorder, acute flaccid myelitis. Although sialic acid has been implicated in EV-D68 entry, the existence of a protein receptor has yet to be clarified. Here we identify neuron-specific intercellular adhesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
96
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(99 citation statements)
references
References 37 publications
1
96
0
2
Order By: Relevance
“…Indeed, similar pathological changes caused by coxsackievirus B3 hippocampal infection have been documented (33). Most interestingly, a recent report on the identification of the EV-D68 receptor suggested that hippocampal neurons are susceptible to EV-D68 (34). It should be noted that induced expression of hWARS could be detected on the plasma membrane of hippocampal neurons in a disease model (32).…”
Section: Discussionmentioning
confidence: 59%
“…Indeed, similar pathological changes caused by coxsackievirus B3 hippocampal infection have been documented (33). Most interestingly, a recent report on the identification of the EV-D68 receptor suggested that hippocampal neurons are susceptible to EV-D68 (34). It should be noted that induced expression of hWARS could be detected on the plasma membrane of hippocampal neurons in a disease model (32).…”
Section: Discussionmentioning
confidence: 59%
“…We also extended this mouse model to studies of a human viral pathogen in the form of enterovirus D68 (EV-D68), a member of the Picornaviridae family that (unlike other enteroviruses) shares characteristics with human rhinovirus (RV) members of this family. In concert with shared viral features, EV-D68 can also cause respiratory infection, and this infection can result in severe illness in susceptible populations, particularly asthmatics (18-23) as well as acute flaccid myelitis in other patients, based possibly on neuronal receptor binding (24). The severity of EV-D68-driven illness might be based on the viral capacity to subvert the IFN-based immune response (25,26), raising the possibility that any further IFN deficiency might no longer influence the infection.…”
mentioning
confidence: 99%
“…Our data indicate that contemporary strains of EV-D68 are better fit to replicate at 37°C than historic strains. Extrapolation of this data suggests that temperature is no barrier for the viruses to infect both upper and lower airways of the human respiratory tract.While recent studies have given insight into the ability of EV-D68 to infect neuronal cell lines in vitro and in animal models as it pertains to receptors, the mechanisms by which EV-D68 infects the central nervous system to cause AFM remain unclear [78][79][80][81][82][83]. Other picornaviruses capable of causing AFM such as poliovirus, EV-71, and CVB all replicate at high physiological temperatures.…”
Section: Discussionmentioning
confidence: 99%